254 Incidence of leiomyosarcoma after the FDA warning against the power morcellator – have we made an impact?. (13th November 2020) - Liao, C; Richardson, M; Tran, K; Chan, C; Mann, AK; Maxwell, GL; Hamilton, CA; Tian, C; Darcy, K; Kapp, DS; Chan, JK
Abstract : Objective: To evaluate the incidence and rates of tumor destruction of uterine leiomyosarcoma (LMS) following the 2014 FDA warning against power morcellators. Methods: Data were obtained from the National Cancer Database (NCDB) to compare rates of tumor destruction over time. LMS incidence rates were estimated from the United States Cancer Statistics (USCS) after correcting for hysterectomy and pregnancy prevalence from the Behavioral Risk Factor Surveillance System (BRFSS) from 2001 to 2016. SEER*Stat and Joinpoint regression were used to calculate the incidence rate (per 100, 000) and average annual percent change (AAPC). Results: Based on USCS, 14, 675 patients were diagnosed with leiomyosarcoma (62% White, 22% Black, 11% Hispanic, 4% Asian). Per NCDB data, the proportion of tumor destruction by minimal invasive surgery in uterine cancer was as high as 3.4% in 2013, but decreased to 2.2% in 2016 after the 2014 FDA warning. Per UCCS data, peak age at leiomyosarcoma diagnosis was nearly a decade younger for Blacks vs. Whites (50–54 vs. 60–64). From 2001 to 2016, Blacks had a two-fold higher incidence compared to whites (1.29 vs. 0.59) and with an annual increase of 3.5% per year compared to a decrease of 0.9% per year in Whites. The incidence rate in 2014 was 0.85 per 100, 000 and decreased to 0.78 and 0.75 in 2015 and 2016. Conclusion: The proportion of tumor destruction by minimal invasive surgery decreased after the 2014 FDA warning against power morcellators. LMS incidence has decreased for Whites but continues to rise for Blacks.